Spectrotemporal weighting of binaural cues: Effects of a diotic interferer on discrimination of dynamic interaural differences - Bibee, Jacqueline M. (J Acoust Soc Am, 2016)
Spatial judgments are often dominated by low-frequency binaural cues and onset cues when binaural cues vary across the spectrum and duration, respectively, of a brief sound. This study combined these dimensions to assess the spectrotemporal weighting of binaural information. Listeners discriminated target interaural time difference (ITD) and interaural level difference (ILD) carried by the onset, offset, or full duration of a 4-kHz Gabor click train with a 2-ms period in the presence or absence of a diotic 500-Hz interferer tone. ITD and ILD thresholds were significantly elevated by the interferer in all conditions and by a similar amount to previous reports for static cues. Binaural interference was dramatically greater for ITD targets lacking onset cues compared to onset and full-duration conditions. Binaural interference for ILD targets was similar across dynamic-cue conditions. These effects mirror the baseline discriminability of dynamic ITD and ILD cues [Stecker and Brown. (2010). J. Acoust. Soc. Am. 127, 3092–3103], consistent with stronger interference for less-robust/higher-variance cues. The results support the view that binaural cue integration occurs simultaneously across multiple variance-weighted dimensions, including time and frequency.